Climate and environmental history of Laguna Polo, Santa Cruz, Southern Patagonia (49°S) since 1300 CE - Charqueño-Celis, Fernanda; Dubois, Nathalie; Zolitschka, Bernd; Pérez, Liseth; Mayr, Christoph; Massaferro, Julieta (Journal of Paleolimnology, 2024)
Patagonia is a unique area for climate studies, exposed to the strong Southern Hemisphere Westerly Winds (SWW) and modulated by the Southern Annular Mode (SAM). Patagonia is also affected by volcanic eruptions of the Andean Mountain Range, and is rich in lacustrine environments, which are ideal for paleocological and paleoclimatological reconstructions. Sediments of Patagonian lakes provide an excellent opportunity to study the responses of aquatic communities to major climatic and environmental events in still pristine freshwater ecosystems. Here, we present a high-resolution paleolimnological reconstruction using testate amoebae and chironomid assemblages and compare it with organic and inorganic sediment geochemistry (Ca, K, Ti, N, TOC, TOC/N, δ15N, δ13C) from a sediment core of Laguna Polo (49°S, Santa Cruz, Argentina) covering the last ca. 1300 years. Our results imply a warm-dry and productive environment from around 1300–1400 CE, a cold and less productive environment from ca. 1400–1700 CE, broadly corresponding to the Little Ice Age (LIA). The latter period is followed by high volcanic activity between ca. 1700 and 1960 CE. The tephra layers are known from other records in the vicinity and are preliminarily attributed to the eruptions of the adjacent Lautaro Volcano. A warm-stenothermic chironomid assemblage indicates a progressive increase in temperature in the most recent time after the last eruption, attributed to Lautaro Volcano in 1960 CE.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Chironomids; Lake sediments; Little Ice Age; Medieval Climate Anomaly; Testate Amoebae